Adhesive composition, and adhesive sheet, laminate, and printed wiring board containing same

By using a bonding composition of a polyester resin, an epoxy resin having nitrogen atoms and an organic phosphinate metal salt, the problems of poor heat resistance of solder and difficulty in meeting the circuit embedding property and resin spillover inhibition in the prior art are solved, and a high-performance bonding agent is realized.

CN119604596APending Publication Date: 2025-03-11东洋纺艾睦希株式会社
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380051820.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-27
Filing Date
2023-10-17
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing adhesives have poor heat resistance in high temperature environments and are difficult to meet the requirements of circuit buried properties and resin overflow at the same time.

Method used

An adhesive composition consisting of a polyester resin and at least two epoxy resins having nitrogen atoms is used, which contains a glycidylamine type epoxy resin, and an organic phosphinate metal salt is added as a flame retardant.

Benefits of technology

It realizes excellent performance of adhesiveness, solder heat resistance and long-term heat resistance, while meeting the requirements of circuit embedding and suppressing resin spillover, and is suitable for automotive applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005227722940000201
    Figure BDA0005227722940000201
  • Figure BDA0005227722940000202
    Figure BDA0005227722940000202
  • Figure BDA0005227722940000203
    Figure BDA0005227722940000203
Patent Text Reader

Abstract

Provided are: an adhesive composition which has excellent adhesiveness and solder heat resistance, exhibits excellent adhesiveness even after being exposed to a high-temperature environment for a long period of time, has good circuit embedding properties, and is capable of suppressing excess resin overflow; and an adhesive sheet, a laminate, and a printed wiring board which contain the adhesive composition. An adhesive composition containing a polyester resin (A) and an epoxy resin (B), the epoxy resin (B) containing at least two epoxy resins (b) having a nitrogen atom, one of the two epoxy resins being (b1) or less and the other being (b2) or less. (b1) a trifunctional or less resin; and (b2) 4 or more functional resins.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive composition. More specifically, it relates to an adhesive composition for bonding a resin substrate to a resin substrate or a metal substrate. In particular, it relates to an adhesive composition for a flexible printed circuit board (hereinafter referred to as FPC) and an adhesive sheet, a laminate and a printed circuit board containing the same. Background Art

[0002] Flexible printed circuits (FPCs) are substrates with circuits formed on a substrate made by bonding a thin and soft film with insulating properties such as polyimide to a conductive metal such as copper foil using an adhesive. Unlike rigid substrates, FPCs are very thin and soft, so they can be used in extremely small gaps and curved movable parts of electronic devices, so they can be used in a variety of electronic devices around us, such as computers and smartphones. In addition, many FPCs are also installed in automobiles, and high long-term heat resistance is often required for adhesives.

[0003] In recent years, as electric vehicles have become more common, the use of high-heat-generating power semiconductors has also increased, and printed circuit board materials used in their installations are required to have higher long-term heat resistance than ever before (for example, Non-Patent Document 1).

[0004] Polyester resins are generally composed of polycarboxylic acids and polyols. Since the flexibility and molecular weight can be freely controlled by selecting and combining polycarboxylic acids and polyols, they are widely used in various applications including coating agents and adhesives.

[0005] Polyester resin has excellent adhesion to copper-containing metals and has been used in adhesives for FPCs after being mixed with a curing agent (for example, Patent Document 1). Prior art literature Patent Literature

[0006] Patent Document 1: Japanese Patent Publication No. 6-104813 Non-patent literature

[0007] Non-patent document 1: Akio Takahashi. Heat-resistant polymer materials for automotive electronic materials. Network Polymer. 2012, 33(1), p.34-41 Summary of the invention Problem that the invention aims to solve

[0008] However, the adhesive using the polyester resin described in Patent Document 1 is inferior in solder heat resistance and does not have the high standard long-term heat resistance required for automotive applications in recent years.

[0009] Furthermore, the adhesive for FPC is required to have the ability to follow the circuit pattern and ensure the circuit embedding property of the insulation between the wirings. Therefore, when the substrate with the circuit formed thereon is thermally pressed and laminated with the substrate with the adhesive layer, a certain degree of adhesive component outflow in the planar direction is required (hereinafter referred to as resin overflow). On the other hand, for excessive resin overflow, the adhesive component flows out from the wiring and covers the areas outside the coating range, which may cause problems such as poor conduction, so it needs to be suppressed. Improving circuit embedding property and suppressing resin overflow are mutually contradictory requirements, so there is a problem that it is difficult to meet both at the same time.

[0010] The present invention is based on the related prior art problems. That is, the purpose of the present invention is to provide an adhesive composition having excellent adhesion and solder heat resistance, further exhibiting excellent adhesion even after long-term exposure to high temperature environment, and having good circuit embedding properties while suppressing excess resin overflow, as well as an adhesive sheet, a laminate and a printed wiring board containing the same. Means to solve problems

[0011] As a result of intensive research, the inventors found that the above-mentioned problems can be solved by the following means, thereby achieving the present invention. That is, the present invention is constituted as follows. [1] An adhesive composition comprising a polyester resin (A) and an epoxy resin (B), wherein the epoxy resin (B) comprises at least two epoxy resins (b) having nitrogen atoms, one of the two epoxy resins being the following epoxy resin (b1) and the other being the following epoxy resin (b2). (b1) Resins with less than 3 functional groups (b2) Resins with four or more functional groups [2] An adhesive composition comprising a polyester resin (A) and an epoxy resin (B), wherein the epoxy resin (B) comprises at least two epoxy resins (b) having nitrogen atoms, one of the two epoxy resins being the following epoxy resin (b3), and the other being the following epoxy resin (b4). (b3) Resin having a nitrogen atom that is not contained in an aromatic ring and is not adjacent to an aromatic ring (b4) Resins having nitrogen atoms other than (b3) [3] The adhesive composition according to [1] or [2], wherein the epoxy resin (b) having a nitrogen atom comprises a glycidylamine-type epoxy resin. [4] The adhesive composition according to any one of [1] to [3], wherein the content of the epoxy resin (B) is 0.1 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the polyester resin (A). [5] The adhesive composition according to any one of [1] to [4], further comprising an organic phosphinate metal salt (C). [6] An adhesive sheet comprising an adhesive layer comprising the adhesive composition according to any one of [1] to [5]. [7] A laminate comprising the adhesive sheet according to [6]. [8] A printed wiring board comprising the laminate described in [7] as a constituent element. Effects of the Invention

[0012] The adhesive composition of the present invention has excellent adhesion, solder heat resistance, and long-term heat resistance, and can satisfy circuit embedding properties and suppress resin overflow. Therefore, it is suitable for FPC adhesives, adhesive sheets, laminates, and printed wiring boards for automotive applications. DETAILED DESCRIPTION

[0013] Hereinafter, one embodiment of the present invention will be described in detail, but the present invention is not limited thereto.

[0014] <Polyester resin (A)> From the viewpoint of satisfying long-term heat resistance, the polyester resin (A) is used as the base resin in the present invention.

[0015] The polyester resin (A) used in the present invention has a chemical structure obtained by a polycondensate of a polycarboxylic acid component and a polyol component, wherein the polycarboxylic acid component and the polyol component are respectively composed of one or more selected components. The polycarboxylic acid component constituting the polyester resin (A) is not particularly limited, and the following polycarboxylic acids or their esters and polycarboxylic anhydrides can be used. Specifically, as the polycarboxylic acid, there can be mentioned: aliphatic polycarboxylic acid, alicyclic polycarboxylic acid, aromatic polycarboxylic acid, etc., as the aliphatic polycarboxylic acid, adipic acid, sebacic acid, dimer acid, 1,2,3,4-butanetetracarboxylic acid, fumaric acid, maleic acid, succinic acid, etc. can be used; as the alicyclic polycarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, tetrahydrophthalic acid, hexahydrophthalic acid, methyltetrahydrophthalic acid, etc. can be used; as the aromatic polycarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, 2,5-furan dicarboxylic acid, dimethyl isophthalic acid-5-sodium sulfonate, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, etc. and their esters, acid anhydrides (pyromellitic anhydride (PMDA) etc.) can be used. In particular, the polyester resin (A) preferably contains monomer units derived from aromatic polycarboxylic acids, wherein as aromatic polycarboxylic acids, naphthalene dicarboxylic acid, terephthalic acid, and isophthalic acid are more preferably included. In 100 mol% of the polycarboxylic acid component constituting the polyester resin (A), the monomer units derived from aromatic polycarboxylic acids are preferably 60 mol% or more, more preferably 85 mol% or more, further preferably 96 mol% or more, and also preferably 100 mol% or less, and may also be 98 mol% or less. By using aromatic polycarboxylic acids, the solder heat resistance of the adhesive composition can be improved.

[0016] The polyol constituting the polyester resin (A) is not particularly limited, and examples thereof include aliphatic polyols, alicyclic polyols, aromatic polyols, etc. As the aliphatic polyol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2-methyl-1,3-propylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 2-methyl-1,3-hexanediol, 2-methyl-2-ethyl-1,3-propylene glycol, 2,2-diethyl-1,3-propylene glycol, 2-ethyl-2-n-propyl-1,3-propylene glycol can be used. , 2,2-di-n-propyl-1,3-propanediol, 2-n-butyl-2-ethyl-1,3-propanediol, 2,2-di-n-butyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, mannitol, sorbitol, dimer glycol, polytetramethylene glycol, polypropylene glycol, pentaerythritol, etc.; as alicyclic polyols, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, α-methyl glucoside, etc. can be used; as aromatic polyols, diphenolic acid, etc. can be used. In particular, the polyester resin (A) preferably contains a monomer unit derived from a polyol having an alkylene group having 4 or more carbon atoms. Examples of the polyol having an alkylene group having 4 or more carbon atoms include 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 2-methyl-1,3-hexanediol, 2,4-diethyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, dimer diol, polytetramethylene glycol, etc., among which 1,4-butanediol and dimer diol are more preferred. In 100 mol% of the polyol component constituting the polyester resin (A), the monomer unit derived from the polyol having an alkylene group having 4 or more carbon atoms is preferably 20 to 80 mol%, more preferably 30 to 65 mol%, and further preferably 40 to 60 mol%. By using a polyol having 4 or more carbon atoms, the bonding strength of the adhesive composition can be improved.

[0017] The polyester resin (A) used in the present invention may be copolymerized with lactone or lactam. For example, ε-caprolactone or ε-caprolactam may be used.

[0018] As methods for the polycondensation reaction of the polyester resin (A) used in the present invention, there are, for example: 1) a method of heating a polycarboxylic acid and a polyol in the presence of a known catalyst, and performing a depolyolation / polycondensation reaction via a dehydration esterification step; 2) a method of heating an alcohol ester of a polycarboxylic acid and a polyol in the presence of a known catalyst, and performing a depolyolation / polycondensation reaction via an ester exchange reaction; 3) a method of performing a depolymerization, etc. In the above methods 1) and 2), part or all of the acid components may be replaced by anhydrides.

[0019] When producing the polyester resin (A) used in the present invention, titanium compounds, antimony compounds, germanium compounds, metal acetates, etc., which are conventionally known polymerization catalysts, can be used. For example, as titanium compounds, tetra-n-butyl titanate, tetra-isopropyl titanate, acetylacetonato titanium oxide, etc. can be used; as antimony compounds, antimony trioxide, antimony tri-butoxide, etc. can be used; as germanium compounds, germanium oxide, tetra-n-butoxygermanium, etc. can be used; as metal acetates, acetates of magnesium, iron, zinc, manganese, cobalt, aluminum, etc. can be used. These catalysts can be used alone or in combination of two or more.

[0020] The number average molecular weight of the polyester resin (A) used in the present invention is preferably less than 100,000, more preferably 50,000 or less, and further preferably 25,000 or less. It is also preferably 3,000 or more, more preferably 5,000 or more, and further preferably 9,000 or more. When it is within the above range, an adhesive composition that is easy to handle when dissolved in a solvent and has excellent adhesiveness can be obtained.

[0021] The glass transition temperature of the polyester resin (A) used in the present invention is preferably 0° C. or higher, more preferably 10° C. or higher, and even more preferably 20° C. or higher. It is also preferably 200° C. or lower, more preferably 100° C. or lower, and even more preferably 50° C. or lower. When it is within the above range, an adhesive composition having excellent adhesiveness can be obtained.

[0022] The acid value of the polyester resin (A) used in the present invention is preferably 50 eq / 10 6 g or more, more preferably 80eq / 10 6 By setting the acid value to 50eq / 10 6 g or more, the reaction points with the epoxy resin (B) can be increased, and after curing, a strong adhesive layer with high crosslinking density is formed, and the solder heat resistance is excellent. The upper limit of the acid value is not particularly limited, but is usually 1000eq / 10 6 g or less, more preferably 500eq / 10 6 g or less, more preferably 400eq / 10 6 g or less.

[0023] As a method for increasing the acid value of the polyester resin (A), there are, for example: (1) after the polycondensation reaction is completed, a method of adding a trivalent or higher polycarboxylic acid and / or a trivalent or higher polycarboxylic acid anhydride to react (acid addition); (2) during the polycondensation reaction, a method of intentionally modifying the resin by the action of heat, oxygen, water, etc., and these methods can be performed arbitrarily. The polyacid anhydride used as the acid addition in the above-mentioned acid addition method is not particularly limited, and examples thereof include: trimellitic anhydride, pyrophthalic anhydride, hexahydrophthalic anhydride, 3,3,4,4-benzophenonetetracarboxylic dianhydride, 3,3,4,4-biphenyltetracarboxylic dianhydride, ethylene glycol ditriphthalic anhydride, etc. These can be used alone or in combination of two or more. Triphthalic anhydride is preferred.

[0024] <Epoxy resin (B)> The epoxy resin (B) used in the present invention contains an epoxy resin (b) having a nitrogen atom. In addition, the "epoxy resin" is not particularly limited as long as it has one or more epoxy groups in the molecule. By using an epoxy resin having a nitrogen atom, long-term heat resistance can be improved.

[0025] The epoxy resin (b) having nitrogen atoms has a higher reactivity with polyester resins than other epoxy resins because the nitrogen atoms in its skeleton act as a catalyst. Due to this high reactivity, the epoxy resin (b) is cured to a certain extent during the coating and drying stages of the adhesive composition on the substrate, and can suppress excess resin overflow when laminating the adhesive composition to a substrate having a circuit formed thereon.

[0026] Epoxy resins (b) having nitrogen atoms specifically include glycidylamine epoxy resins, triazine derivative epoxy resins, and the like. In order to significantly obtain the effects of the present invention, glycidylamine epoxy resins are preferred. Glycidylamine epoxy resins specifically include aliphatic glycidylamine epoxy resins, alicyclic glycidylamine epoxy resins, aromatic glycidylamine epoxy resins, and the like. As alicyclic glycidylamine epoxy resins, 1,3-bis(diglycidylaminomethyl)cyclohexane and the like can be used; as aromatic glycidylamine epoxy resins, N,N-diglycidylaniline, N,N-diglycidylaniline and the like can be used. Oleyl-o-toluidine, N,N,O-triglycidyl-p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, N,N,N',N'-tetraglycidyl-(4,4'-methylenedianiline), N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-m-phenylenediamine, etc.

[0027] Specific examples of the triazine derivative epoxy resin include 1,3,5-triglycidyl-S-triazinetrione and the like.

[0028] The adhesive composition of the present invention is characterized by containing at least two epoxy resins (b) having nitrogen atoms. By using at least two epoxy resins (b) having nitrogen atoms together, it is possible to satisfy circuit embedding properties and suppression of resin overflow without losing long-term heat resistance.

[0029] Regarding the epoxy resin (b) having nitrogen atoms, for the above two types, from the viewpoints of circuit embedding, suppression of resin overflow and long-term heat resistance, it is particularly preferred that one is a resin with three or less functional groups (hereinafter referred to as b1) and the other is a resin with four or more functional groups (hereinafter referred to as b2). Here, the number of functions refers to the number of epoxy groups in one molecule. Circuit embedding and suppression of excess resin overflow are in a trade-off relationship. When only (b1) is used, the circuit embedding is poor; when only (b2) is used, the suppression of resin overflow is insufficient. From the viewpoints of circuit embedding and suppression of excess resin overflow, (b1) and (b2) are mixed.

[0030] For (b1), specific examples include: N,N-diglycidylaniline, N,N-diglycidyl-o-toluidine, N,N,O-triglycidyl-p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, 1,3,5-triglycidyl-S-triazinetrione, etc.; for (b2), specific examples include: 1,3-bis(diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-(4,4'-methylenedianiline), N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-m-xylenediamine, etc.

[0031] When (b1) is used as the epoxy resin (b) having a nitrogen atom, the content of (b1) in 100 parts by mass of the epoxy resin (b) having a nitrogen atom is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and further preferably 50 parts by mass or more. In addition, it is preferably 80 parts by mass or less, more preferably 75 parts by mass or less, and further preferably 70 parts by mass or less. By setting it within the above range, the balance between circuit embedding property and suppression of resin overflow is particularly good.

[0032] When (b2) is used as the epoxy resin (b) having a nitrogen atom, the content of (b2) in 100 parts by mass of the epoxy resin (b) having a nitrogen atom is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and further preferably 30 parts by mass or more. In addition, it is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, and further preferably 50 parts by mass or less. By setting it within the above range, the balance between circuit embedding and suppression of resin overflow is particularly good.

[0033] The content of (b1) is preferably 20 parts by mass or more and 300 parts by mass or less, more preferably 60 parts by mass or more and 250 parts by mass or less, and further preferably 120 parts by mass or more and 240 parts by mass or less relative to 100 parts by mass of (b2). By setting it within the above range, the balance between circuit embedding property and suppression of resin overflow is particularly good.

[0034] For the epoxy resin (b) having nitrogen atoms, from the viewpoint of circuit embedding property and suppression of resin overflow, it is particularly preferred that one of the above two types is a resin having nitrogen atoms not contained in an aromatic ring and not adjacent to an aromatic ring (hereinafter referred to as b3), and the other is a resin having nitrogen atoms other than (b3) (hereinafter referred to as b4), that is, a resin having nitrogen atoms contained in an aromatic ring or adjacent to an aromatic ring. The reason for this is not clear, but it is believed that the catalytic effect of the nitrogen atoms in the skeleton of (b3) has a greater influence than that of (b4), and it is presumed that by mixing (b3) and (b4), it is easy to strike a balance between circuit embedding property and suppression of excess resin overflow.

[0035] Specific examples of (b3) include 1,3-bis(diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-m-xylenediamine, etc. Specific examples of (b4) include N,N-diglycidylaniline, N,N-diglycidyl-o-toluidine, N,N,O-triglycidyl-p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, N,N,N',N'-tetraglycidyl-(4,4'-methylenedianiline), N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, and 1,3,5-triglycidyl-S-triazinetrione.

[0036] When (b3) is used as the epoxy resin (b) having a nitrogen atom, the content of (b3) in 100 parts by mass of the epoxy resin (b) having a nitrogen atom is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and further preferably 30 parts by mass or more. In addition, it is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, and further preferably 50 parts by mass or less. By setting it within the above range, the balance between circuit embedding and suppression of resin overflow is particularly good.

[0037] When (b4) is used as the epoxy resin (b) having a nitrogen atom, the content of (b4) in 100 parts by mass of the epoxy resin (b) having a nitrogen atom is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and further preferably 50 parts by mass or more. In addition, it is preferably 80 parts by mass or less, more preferably 75 parts by mass or less, and further preferably 70 parts by mass or less. By setting it within the above range, the balance between circuit embedding and suppression of resin overflow is particularly good.

[0038] The content of (b3) is preferably 20 parts by mass or more and 300 parts by mass or less, more preferably 30 parts by mass or more and 200 parts by mass or less, and further preferably 40 parts by mass or more and 90 parts by mass or less relative to 100 parts by mass of (b4). By setting it within the above range, the balance between circuit embedding property and suppression of resin overflow is particularly good.

[0039] For the epoxy resin (b) having nitrogen atoms, it is particularly preferred that one of the two types is a resin having two or more nitrogen atoms and the other is a resin having one nitrogen atom from the viewpoint of circuit embedding property and suppression of resin overflow. For the resin having two or more nitrogen atoms, specifically, as the glycidylamine type epoxy resin, 1,3-bis(diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-(4,4'-methylenedianiline), N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, etc. can be cited; as the triazine derivative epoxy resin, 1,3,5-triglycidyl-S-triazinetrione, etc. can be cited. Specific examples of the resin having one nitrogen atom include N,N-diglycidylaniline, N,N-diglycidyl-o-toluidine, N,N,O-triglycidyl-p-aminophenol, and N,N,O-triglycidyl-4-amino-3-methylphenol.

[0040] When a resin having one nitrogen atom is used as the epoxy resin (b) having a nitrogen atom, the content of the resin having one nitrogen atom in 100 parts by mass of the epoxy resin (b) having a nitrogen atom is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and further preferably 50 parts by mass or more. In addition, it is preferably 80 parts by mass or less, more preferably 75 parts by mass or less, and further preferably 70 parts by mass or less. By setting it within the above range, the balance between circuit embedding property and suppression of resin overflow is particularly good.

[0041] When a resin having two or more nitrogen atoms is used as the epoxy resin (b) having nitrogen atoms, the content of the resin having two or more nitrogen atoms in 100 parts by mass of the epoxy resin (b) having nitrogen atoms is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 30 parts by mass or more. In addition, it is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, and even more preferably 50 parts by mass or less. By setting it within the above range, the balance between circuit embedding property and suppression of resin overflow is particularly good.

[0042] The content of the resin having one nitrogen atom is preferably 20 parts by mass or more and 300 parts by mass or less, more preferably 60 parts by mass or more and 250 parts by mass or less, and even more preferably 120 parts by mass or more and 240 parts by mass or less relative to 100 parts by mass of the resin having two or more nitrogen atoms. By setting the content within the above range, the balance between circuit embedding property and suppression of resin overflow is particularly good.

[0043] In the adhesive composition of the present invention, the content of the epoxy resin (b) having nitrogen atoms is preferably 40 parts by mass or more, more preferably 60 parts by mass or more, further preferably 70 parts by mass or more, and may be 100 parts by mass in 100 parts by mass of the epoxy resin (B). By setting it to be above the above lower limit, long-term heat resistance is particularly good.

[0044] The adhesive composition of the present invention may also contain epoxy resins other than the epoxy resin (b) having nitrogen atoms. As epoxy resins other than the epoxy resin (b) having nitrogen atoms, there is no particular limitation as long as there is an epoxy group in the molecule, and preferably there are two or more epoxy groups in the molecule. Specifically, there is no particular limitation, and at least one selected from the group consisting of biphenyl epoxy resins, naphthalene epoxy resins, bisphenol A epoxy resins, bisphenol F epoxy resins, novolac epoxy resins, alicyclic epoxy resins, dicyclopentadiene epoxy resins, dimer acid-modified epoxy resins, and epoxidized modified polybutadiene can be used.

[0045] In the adhesive composition of the present invention, relative to 100 parts by mass of polyester resin (A), the content of epoxy resin (B) is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more. By setting it to above the above lower limit, a sufficient curing effect can be obtained, showing excellent adhesion and solder heat resistance. In addition, it is preferably below 20 parts by mass, more preferably below 10 parts by mass. By setting it to below the above upper limit, long-term heat resistance is good. That is, by setting it within the above range, an adhesive composition with more excellent adhesion, solder heat resistance and long-term heat resistance can be obtained.

[0046] <Flame retardant> The adhesive composition of the present invention may contain a flame retardant. The flame retardant is not particularly limited, and examples thereof include organic phosphorus compounds and organic phosphinate metal salts (C). From the viewpoint of achieving both flame retardancy and long-term heat resistance, organic phosphinate metal salts (C) are preferred in order to have particularly significant effects.

[0047] Specific examples of the organic phosphorus compound include 9,10-dihydro-10-benzyl-9-oxa-10-phosphaphenanthrene-10-oxide and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0048] Specific examples of the organic phosphinate metal salt include dimethylphosphinate, ethylmethylphosphinate, diethylphosphinate, methyl-n-propylphosphinate, methylphenylphosphinate, diphenylphosphinate, methanedi(methylphosphinate) salt, and benzene-1,4-di(methylphosphinate) salt. As dimethyl phosphinate, magnesium dimethyl phosphinate, calcium dimethyl phosphinate, zinc dimethyl phosphinate, aluminum dimethyl phosphinate, etc. can be used; as ethylmethyl phosphinate, magnesium ethylmethyl phosphinate, calcium ethylmethyl phosphinate, zinc ethylmethyl phosphinate, aluminum ethylmethyl phosphinate, etc. can be used; as diethyl phosphinate, magnesium diethyl phosphinate, calcium diethyl phosphinate, zinc diethyl phosphinate, aluminum diethyl phosphinate, etc. can be used; as methyl-n-propyl phosphinate, magnesium methyl-n-propyl phosphinate, calcium methyl-n-propyl phosphinate, zinc methyl-n-propyl phosphinate, aluminum methyl-n-propyl phosphinate, etc. can be used; as methylphenyl phosphinate, magnesium methylphenyl phosphinate, methylphenyl phosphinate, etc. can be used. As diphenylphosphinates, magnesium diphenylphosphinate, calcium diphenylphosphinate, zinc diphenylphosphinate, aluminum diphenylphosphinate, etc. can be used; as diphenylphosphinates, magnesium diphenylphosphinate, calcium diphenylphosphinate, zinc diphenylphosphinate, aluminum diphenylphosphinate, etc. can be used; as methanedi(methylphosphinate) salts, magnesium methanedi(methylphosphinate), calcium methanedi(methylphosphinate), zinc methanedi(methylphosphinate), aluminum methanedi(methylphosphinate), etc. can be used; as benzene-1,4-di(methylphosphinate) salts, magnesium benzene-1,4-di(methylphosphinate), calcium benzene-1,4-di(methylphosphinate), zinc benzene-1,4-di(methylphosphinate), aluminum benzene-1,4-di(methylphosphinate), etc. can be used.

[0049] When the adhesive composition of the present invention contains a flame retardant, the content of the flame retardant is preferably 1 to 40 parts by mass, more preferably 5 to 20 parts by mass, relative to 100 parts by mass of the polyester resin (A). By setting it above the lower limit, an adhesive composition with excellent flame retardancy can be manufactured; by setting it below the upper limit, it is advantageous in terms of manufacturing cost.

[0050] <Organic Solvents> The adhesive composition of the present invention may further contain an organic solvent. The organic solvent used in the present invention is not particularly limited as long as it can dissolve the polyester resin (A) and the epoxy resin (B). Specifically, there are: aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, halogenated hydrocarbons, alcohol solvents, ketone solvents, ester solvents, glycol ether solvents, etc. As aromatic hydrocarbons, benzene, toluene, xylene, etc. can be used; as aliphatic hydrocarbons, hexane, heptane, octane, decane, etc. can be used; as alicyclic hydrocarbons, cyclohexane, cyclohexene, methylcyclohexane, ethylcyclohexane, etc. can be used; as halogenated hydrocarbons, trichloroethylene, dichloroethylene, chlorobenzene, chloroform, etc. can be used; as alcohol solvents, methanol, ethanol, isopropanol, butanol, pentanol, hexanol, propylene glycol, phenol can be used. As ketone solvents, acetone, methyl isobutyl ketone, methyl ethyl ketone, amyl ketone, hexanone, cyclohexanone, isophorone, acetophenone, etc. can be used; as ester solvents, methyl acetate, ethyl acetate, butyl acetate, methyl propionate, butyl formate, etc. can be used; as glycol ether solvents, ethylene glycol monomethyl ether, ethylene glycol mono-n-butyl ether, ethylene glycol mono-isobutyl ether, ethylene glycol mono-tert-butyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol mono-isobutyl ether, triethylene glycol mono-n-butyl ether, tetraethylene glycol mono-n-butyl ether, etc. can be used, and these can be used alone or in combination of two or more. In particular, from the perspective of working environment and dryness, aromatic hydrocarbons or ketone solvents are preferred, and toluene and methyl ethyl ketone are more preferred.

[0051] When the adhesive composition of the present invention contains an organic solvent, the content of the organic solvent is preferably in the range of 100 to 1000 parts by mass relative to 100 parts by mass of the polyester resin (A). By setting it to be above the above lower limit, the liquid properties and pot life are good. In addition, by setting it to be below the above upper limit, it is advantageous in terms of manufacturing cost and transportation cost.

[0052] The adhesive composition of the present invention may further contain other components as required. Specific examples of such components include a tackifier, a filler, and a silane coupling agent.

[0053] <Thickener> The adhesive composition of the present invention may also be mixed with a tackifier as needed. Examples of the tackifier include polyterpene resins, rosin-based resins, aliphatic petroleum resins, alicyclic petroleum resins, copolymerized petroleum resins, styrene resins, and hydrogenated petroleum resins, which can be used for the purpose of improving bonding strength. These can be used alone or in any combination of two or more. When the tackifier is contained, it is preferably contained in the range of 1 to 200 parts by mass, more preferably in the range of 5 to 150 parts by mass, and most preferably in the range of 10 to 100 parts by mass, relative to a total of 100 parts by mass of the polyester resin (A) and the epoxy resin (B). By setting it within the above range, the effect of the tackifier can be exhibited while maintaining adhesion and solder heat resistance.

[0054] <Packing> Fillers may be mixed into the adhesive composition of the present invention as needed. Examples of fillers include organic fillers and inorganic fillers. As organic fillers, powders of heat-resistant resins such as polyimide, polyamide-imide, fluororesin, and liquid crystal polyester may be used; as inorganic fillers, silicon dioxide (SiO2), aluminum oxide (Al2O3), titanium oxide (TiO2), tantalum oxide (Ta2O5), zirconium oxide (ZrO2), silicon nitride (Si3N4), boron nitride (BN), calcium carbonate (CaCO3), calcium sulfate (CaSO4), zinc oxide (ZnO), magnesium titanate (MgO·TiO2), barium sulfate (BaSO4), organic bentonite, clay, mica, aluminum hydroxide, and magnesium hydroxide may be used. Among them, silicon dioxide is preferred from the perspective of ease of dispersion and the effect of improving solder heat resistance. As silica, hydrophobic silica and hydrophilic silica are generally known, wherein for imparting hygroscopic resistance, hydrophobic silica treated with dimethyldichlorosilane, hexamethyldisilazane, octylsilane, etc. is preferably used. When the filler is mixed, the mixed amount is preferably 0.05 to 50 parts by mass relative to a total of 100 parts by mass of the polyester resin (A) and the epoxy resin (B). By setting it to more than the above lower limit, better solder heat resistance can be shown. In addition, by setting it to less than the above upper limit, poor dispersion of the filler and excessive solution viscosity can be suppressed, and the processability is good.

[0055] <Silane coupling agent> In the adhesive composition of the present invention, a silane coupling agent may be mixed as needed. Since the adhesion to metal and the solder heat resistance can be improved by mixing the silane coupling agent, it is very preferred. There is no particular limitation on the silane coupling agent, and examples include: a silane coupling agent with an unsaturated group, a silane coupling agent with an epoxy group, a silane coupling agent with an amino group, etc. Among these, from the viewpoint of solder heat resistance, a silane coupling agent with an epoxy group is further preferred, for example, γ-glycidyloxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltriethoxysilane, etc. can be used. When the silane coupling agent is mixed, the mixing amount is preferably 0.5 to 20 parts by mass relative to a total of 100 parts by mass of the polyester resin (A) and the epoxy resin (B). By setting it within the above range, solder heat resistance and adhesion can be improved.

[0056] <Laminate> The laminate of the present invention is a laminate of a laminated substrate and an adhesive composition (a 2-layer laminate of substrate / adhesive layer), or a laminate of a further laminated substrate (a 3-layer laminate of substrate / adhesive layer / substrate). Wherein, the adhesive layer refers to the adhesive composition layer after the adhesive composition of the present invention is applied to the substrate and dried. The laminate of the present invention can be obtained by applying the adhesive composition of the present invention to various substrates, drying and further laminating other substrates according to conventional methods.

[0057] <Base Material> In the present invention, the so-called substrate is not particularly limited as long as it can be coated with the adhesive composition of the present invention and form an adhesive layer after drying, and can include: resin substrates such as film-like resins, metal substrates such as metal plates and metal foils, paper, etc. In addition, the substrate in the present invention can also be composed of a composite material.

[0058] Examples of the resin substrate include polyester resins, polyamide resins, polyimide resins, polyamideimide resins, liquid crystal polymers, polyphenylene sulfide, syndiotactic polystyrene, polyolefin resins, and fluorine resins, etc. Film-like resins (hereinafter also referred to as substrate film layers) are preferred.

[0059] As a metal substrate, any known conductive material that can be used for a circuit board can be used. As materials, various metals such as SUS, copper, aluminum, iron, steel, zinc, nickel, and their respective alloys, electroplated products, metals treated with other metals such as zinc and chromium compounds, etc. are listed. It is preferably a metal foil, and more preferably a copper foil. There is no particular limitation on the thickness of the metal foil, preferably 1 μm or more, more preferably 3 μm or more, and more preferably 10 μm or more. In addition, it is preferably 50 μm or less, more preferably 30 μm or less, and more preferably 20 μm or less. When the thickness is too thin, it is difficult to obtain sufficient electrical performance in the circuit. On the other hand, when the thickness is too thick, there is a situation where the processing efficiency during circuit production is reduced. The metal foil is usually provided in a roll form. The form of the metal foil used in the manufacture of the printed wiring board of the present invention is not particularly limited. When a strip-shaped metal foil is used, its length is not particularly limited. In addition, its width is not particularly limited, and it is preferably about 250 to 500 cm. The surface roughness of the substrate is not particularly limited, but is preferably 3 μm or less, more preferably 2 μm or less, and further preferably 1.5 μm or less. In terms of practicality, it is preferably 0.3 μm or more, more preferably 0.5 μm or more, and further preferably 0.7 μm or more.

[0060] Examples of paper include woodfree paper, kraft paper, toilet paper, glassine paper, etc. Examples of composite materials include glass epoxy resin, etc.

[0061] From the perspective of adhesion to the adhesive composition and durability, the substrate is preferably a polyester resin, a polyamide resin, a polyimide resin, a polyamideimide resin, a liquid crystal polymer, polyphenylene sulfide, syndiotactic polystyrene, a polyolefin resin, a fluorine resin, a SUS steel plate, a copper foil, an aluminum foil or a glass epoxy resin.

[0062] <Adhesive Sheet> In the present invention, the adhesive sheet is a sheet formed by laminating the above-mentioned substrate and the release substrate via an adhesive composition. As a specific configuration, it can be mentioned: substrate / adhesive layer / release substrate, or release substrate / adhesive layer / substrate / adhesive layer / release substrate. By laminating the release substrate, it can function as a protective layer of the adhesive layer. In addition, by using a release substrate, the release substrate can be demolded from the adhesive sheet, and the adhesive layer can be further transferred to another substrate.

[0063] By following a conventional method, adhesive composition of the present invention is applied to various laminates, and adhesive sheet of the present invention can be obtained after drying. In addition, when release substrate is attached to adhesive layer after drying, it can be rolled up without causing adhesion to substrate, and when operability is excellent, because adhesive layer is protected, preservation is excellent, and use is also easy. In addition, it is applied to release substrate, and after drying, when other release substrates are adhered as required, adhesive layer itself can also be transferred to other substrates.

[0064] <Release substrate> There is no particular limitation on the release substrate, and examples thereof include substrates in which a coating layer of a pore-filling agent such as clay, polyethylene, or polypropylene is provided on both sides of paper such as woodfree paper, kraft paper, toilet paper, or glassine paper, and a silicone-based, fluorine-based, or alkyd-based release agent is further coated on each of the coating layers. In addition, various olefin films such as polyethylene, polypropylene, ethylene-α-olefin copolymer, and propylene-α-olefin copolymer, and substrates in which the above-mentioned release agent is coated on a film such as polyethylene terephthalate can be cited. For reasons such as the release force between the release substrate and the adhesive layer, and the negative impact of silicone on electrical properties, it is preferred to perform a polypropylene pore-filling treatment on both sides of woodfree paper, and then use an alkyd-based release agent on this basis, or to use an alkyd-based release agent on polyethylene terephthalate.

[0065] It should be noted that, as a method for coating the adhesive composition on the substrate in the present invention, there is no particular limitation, and examples include: a comma coater, a reverse roll coater, and the like. Alternatively, as required, an adhesive layer may be provided directly or by a transfer method on a rolled copper foil or a polyimide film as a constituent material of a printed wiring board. For the thickness of the adhesive layer after drying, appropriate changes are made as required, preferably in the range of 5 to 200 μm. By setting the adhesive film thickness to be 5 μm or more, sufficient bonding strength can be obtained. In addition, by setting the adhesive film thickness to be 200 μm or less, the amount of residual solvent in the drying process can be easily controlled, and bubbling is difficult to occur when pressing the printed wiring board. The drying conditions are not particularly limited, and the residual solvent rate after drying is preferably 1% by mass or less. By setting it to 1% by mass or less, the bubbling of the residual solvent during pressing the printed wiring board can be suppressed, and bubbling is difficult to occur.

[0066] <Printed circuit board> The printed wiring board in the present invention contains a laminate formed by a metal foil forming a conductor circuit and a resin substrate as a constituent element. For example, a metal-clad laminate can be used to manufacture a printed wiring board by a conventionally known method such as a subtractive method. The so-called flexible printed circuit (FPC), flat cable, tape automated bonding (TAB) circuit board, etc., which are partially or completely coated with a cover film, screen printing ink, etc., as required, and are collectively referred to as printed wiring boards.

[0067] The printed wiring board of the present invention may be any laminated structure that can be used as a printed wiring board. For example, it may be a printed wiring board consisting of four layers of a substrate film layer, a metal foil layer, an adhesive layer, and a cover film layer. In addition, for example, it may be a printed wiring board consisting of five layers of a substrate film layer, an adhesive layer, a metal foil layer, an adhesive layer, and a cover film layer.

[0068] Furthermore, as required, the structure may be a stack of two or three or more printed wiring boards.

[0069] The adhesive composition of the present invention can be applied to each adhesive layer of a printed wiring board. In particular, when the adhesive composition of the present invention is used as an adhesive, it can have high adhesion to existing resin substrates such as polyimide, polyester film, copper foil, aluminum foil, etc. constituting a printed wiring board, and can obtain reflow resistance. Therefore, it is suitable as an adhesive composition for coverlay films, laminates, copper foil with resin, adhesive sheets, and reinforcing materials.

[0070] In the printed wiring board of the present invention, any resin film that has been used as a printed wiring board substrate can be used as the substrate film. Examples of the resin of the substrate film include polyester resins, polyamide resins, polyimide resins, polyamideimide resins, liquid crystal polymers, polyphenylene sulfide, syndiotactic polystyrene, polyolefin resins, and fluorine resins.

[0071] <Cover film> As the cover film, any known insulating film can be used as the insulating film for printed wiring boards. For example, films made of various polymers such as polyimide, polyester, polyphenylene sulfide, polyether sulfone, polyether ether ketone, aramid fiber, polycarbonate, polyarylate, polyamide-imide, liquid crystal polymer, syndiotactic polystyrene, and polyolefin resin can be used. Polyimide film is more preferred.

[0072] In addition to using the above-mentioned materials for each layer, the printed wiring board of the present invention can be manufactured by any conventionally known process.

[0073] In a preferred embodiment, a semi-finished product (hereinafter referred to as "semi-finished product on the cover film side") is manufactured by laminating an adhesive layer on a cover film layer. On the other hand, a semi-finished product (hereinafter referred to as "semi-finished product on the base film side 2-layer") is manufactured by laminating a metal foil layer on a base film layer to form a desired circuit pattern, or a semi-finished product (hereinafter referred to as "semi-finished product on the base film side 3-layer") is manufactured by laminating an adhesive layer on a base film layer and then laminating a metal foil layer thereon to form a desired circuit pattern (hereinafter referred to as "semi-finished product on the base film side 2-layer") (hereinafter, the semi-finished product on the base film side 3-layer and the semi-finished product on the base film side are collectively referred to as "semi-finished product on the base film side"). By laminating the semi-finished product on the cover film side and the semi-finished product on the base film side thus obtained, a printed wiring board with 4 or 5 layers can be obtained.

[0074] For the semi-finished product on the substrate film side, for example, it can be obtained by a manufacturing method including (A) coating a resin solution constituting the substrate film on the above-mentioned metal foil, and initially drying the coating film, and (B) heat treating / drying the laminate of the metal foil and the initially dried coating film obtained in (A) (hereinafter referred to as the "heat treatment / desolventization step").

[0075] The circuit in the metal foil layer can be formed using a conventionally known method, either an additive method or a subtractive method, preferably a subtractive method.

[0076] The obtained substrate film side semi-finished product may be used for lamination with the cover film side semi-finished product as it is, or may be used for lamination with the cover film side semi-finished product after lamination and storage with a release film.

[0077] The semi-finished product on the cover film side can be produced, for example, by coating an adhesive on the cover film. A cross-linking reaction can be performed during the coating of the adhesive as required. In a preferred embodiment, the adhesive layer is semi-cured.

[0078] The obtained cover film side semi-finished product may be used for lamination with the substrate film side semi-finished product as it is, or may be used for lamination with the substrate film side semi-finished product after being laminated and stored with a release film.

[0079] The semi-finished product on the substrate film side and the semi-finished product on the cover film side can be laminated after being stored in the form of rolls, for example, to manufacture a printed circuit board. As a laminating method, any method can be used, for example, laminating by pressing or rollers. In addition, the two can be laminated while heating by using a hot press or a heated roller device.

[0080] For the semi-finished product on the reinforcing material side, for example, in the case of a soft and reelable reinforcing material such as a polyimide film, it is suitable to apply an adhesive on the reinforcing material and manufacture it. In addition, in the case of a relatively hard reinforcing plate that cannot be reeled, such as a metal plate such as SUS, aluminum, or a plate after glass fiber is cured using epoxy resin, it is preferably manufactured by transfer coating an adhesive pre-coated on a demoulding substrate. In addition, as required, a cross-linking reaction in the applied adhesive can be performed. In a preferred embodiment, the adhesive layer is semi-cured.

[0081] The obtained reinforcing material side semi-finished product can be directly used for lamination to the back surface of the printed wiring board, or can be used for lamination to the substrate film side semi-finished product after being laminated and stored with a release film.

[0082] The semi-finished product on the substrate film side, the semi-finished product on the cover film side, and the semi-finished product on the reinforcing material side are all the laminated bodies for printed wiring boards in the present invention.

[0083] This application claims the benefit of priority based on Japanese Patent Application No. 2022-172590 filed on October 27, 2022. The entire contents of the specification of Japanese Patent Application No. 2022-172590 filed on October 27, 2022 are incorporated herein by reference. Example

[0084] Hereinafter, the present invention will be specifically described with reference to Examples. It should be noted that "parts" in the Examples and Comparative Examples are parts by mass.

[0085] (Physical property evaluation method) (Determination of the composition of polyester resin (A)) Using 400MHz 1 The molar ratio of the polycarboxylic acid component and the polyol component constituting the polyester resin (A) is quantitatively measured using a H-nuclear magnetic resonance hydrogen spectrometer (hereinafter referred to as NMR). Deuterated chloroform is used as the solvent. It should be noted that when the acid value of the polyester resin (A) is increased by acid post-addition, the molar ratio of each component is calculated based on the total amount of the acid components other than the acid components used for acid post-addition being 100 mol%.

[0086] (Determination of glass transition temperature) The measurement was performed using a differential scanning calorimeter (SII, DSC-200). 5 mg of the sample (polyester resin (A)) was placed in an aluminum lid-type container and sealed, and cooled to -50°C using liquid nitrogen. The temperature was then raised to 150°C at a rate of 20°C / min. In the endothermic curve obtained during the heating process, the intersection temperature of the extension line of the baseline before the endothermic peak (below the glass transition temperature) and the tangent line of the endothermic peak (the tangent line showing the maximum slope between the rising part of the peak and the peak apex) was the glass transition temperature (unit: °C).

[0087] (Determination of number average molecular weight) The polyester resin (A) sample was dissolved and / or diluted with tetrahydrofuran to a resin concentration of about 0.5 mass %, and the sample filtered through a polytetrafluoroethylene membrane filter with a pore size of 0.5 μm was used as a sample for measurement. The molecular weight was determined by gel permeation chromatography (GPC) using tetrahydrofuran as the mobile phase and a differential refractometer as the detector. The flow rate was 1 mL / min and the column temperature was 30°C. The chromatographic columns used were KF-802, 804L, and 806L manufactured by Showa Denko. Monodisperse polystyrene was used as the molecular weight standard.

[0088] The following is a synthesis example of the polyester resin (A) used in the present invention.

[0089] (Production Example of Polyester Resin (a1)) A reaction vessel equipped with a stirrer, a condenser, and a thermometer was charged with 20.93 parts of terephthalic acid, 0.81 parts of trimellitic anhydride, 43.25 parts of isophthalic acid, 4.25 parts of sebacic acid, 2.41 parts of diphenolic acid, 24.51 parts of 2-methyl-1,3-propanediol, 13.78 parts of 1,4-cyclohexanedimethanol, 33.11 parts of 1,4-butanediol, and 0.03 mol% of tetrabutyl titanate as a catalyst relative to the total polycarboxylic acid components, and the temperature was raised from 160° C. to 220° C. over 4 hours to carry out an esterification reaction while passing through a dehydration step. In the subsequent polycondensation reaction step, the system was depressurized to 5 mmHg over 20 minutes, and the temperature was further raised to 250° C. Then, the pressure was reduced to below 0.3 mmHg, and after a 60-minute polycondensation reaction, the reaction was cooled to 220°C, 0.82 parts of trimellitic anhydride and 0.88 parts of ethylene glycol di-trimellitic anhydride were added, and the reaction was continued for 30 minutes, and the mixture was taken out. According to the results of the composition analysis of NMR, the obtained polyester resin (a1) was a copolymerized polyester with a molar ratio of terephthalic acid / isophthalic acid / sebacic acid / bisphenol acid / trimellitic anhydride / 2-methyl-1,3-propanediol / 1,4-butanediol / 1,4-cyclohexanedimethanol / trimellitic anhydride / ethylene glycol di-trimellitic anhydride = 30 / 62 / 5 / 2 / 1 / 28 / 55 / 17 / 1 / 0.5. In addition, the glass transition temperature was 35°C, and the acid value was 150eq / 10 6 g, and the number average molecular weight was 14,200.

[0090] (Production Example of Polyester Resin (a2)) A reaction vessel equipped with a stirrer, a condenser, and a thermometer was charged with 54.79 parts of terephthalic acid, 20.60 parts of isophthalic acid, 0.79 parts of trimellitic anhydride, 11.54 parts of ethylene glycol, 45.20 parts of neopentyl glycol, and 0.05 mol% of tetrabutyl titanate as a catalyst relative to the total polycarboxylic acid components, and the temperature was raised from 160°C to 220°C over 4 hours, and an esterification reaction was carried out while passing through a dehydration step. Then, in the polycondensation reaction step, the pressure in the system was reduced to 5 mmHg over 20 minutes, and the temperature was further raised to 250°C. Then, the pressure was reduced to 0.3 mmHg or less, and a polycondensation reaction was carried out for 60 minutes, and then the reaction was cooled to 220°C, and 0.79 parts of trimellitic anhydride was added, reacted for 30 minutes, and then taken out. According to the results of NMR composition analysis, the obtained polyester resin (a2) was a copolymerized polyester with a molar ratio of terephthalic acid / isophthalic acid / trimellitic anhydride / ethylene glycol / neopentyl glycol / trimellitic anhydride = 69 / 30 / 1 / 30 / 70 / 1. In addition, the glass transition temperature was 63°C and the acid value was 100 eq / 10 6 g, and the number average molecular weight is 10,000.

[0091] (Production Example of Polyamide-Imide (d1)) Into a four-necked separable flask equipped with a stirrer, a cooling tube, a nitrogen inlet tube and a thermometer, 105.67 g of trimellitic anhydride, 80.09 g of sebacic acid, 175 g of acrylonitrile-butadiene rubber with carboxylic acids at both ends (CTBN1300×13, number average molecular weight 3500, acrylonitrile ratio 26 wt%), 252.75 g of 4,4'-diphenylmethane diisocyanate, and 526 g of dimethylacetamide were charged, and the temperature was raised to 100°C under a nitrogen stream and allowed to react for 2 hours. Then, 117 g of dimethylacetamide was added, and after further reacting at 150°C for 5 hours, 439 g of toluene and 146 g of dimethylacetamide were added for dilution, and the mixture was cooled to room temperature to obtain a brown polyamide-imide resin solution (d1) with no turbidity. In addition, the glass transition temperature was 145°C, and the acid value was 463 eq / 10 6 g, and the number average molecular weight is 20,000.

[0092] (Production Example of Acid-modified Polypropylene (e1)) 100 parts by mass of propylene-butene copolymer ("TAFMER (registered trademark) XM7080" manufactured by Mitsui Chemicals, Inc.), 150 parts by mass of toluene, 19 parts by mass of maleic anhydride, and 6 parts by mass of di-tert-butyl peroxide were added to a 1L autoclave, and the temperature was raised to 140°C, followed by further stirring for 3 hours. After that, the obtained reaction solution was cooled, and then injected into a container into which a large amount of methyl ethyl ketone was added to precipitate the resin. Thereafter, the acid-modified propylene-butene copolymer grafted with maleic anhydride was separated and purified from the (poly)maleic anhydride and low molecular weight substances by centrifuging the liquid containing the resin. Thereafter, the maleic anhydride-modified propylene-butene copolymer (e1) was obtained by drying at 70°C under reduced pressure for 5 hours. In addition, the acid value was 338 eq / 10 6 g, number average molecular weight of 25,000, and melting point of 80°C.

[0093] The following is a production example of the adhesive composition of the embodiment of the present invention and the adhesive composition of the comparative example. In addition, the following substances were used as epoxy resin (B). EP-3950E: (N,N,O-triglycidyl-p-aminophenol, manufactured by ADEKA Corporation) [Chemistry 1] TETRAD X: (N,N,N',N'-tetraglycidyl-m-xylylenediamine, manufactured by Mitsubishi Gas Chemical Co., Ltd.) [Chemistry 2] jER604: (N,N,N',N'-tetraglycidyl-(4,4'-methylenedianiline), manufactured by Mitsubishi Chemical Corporation) [Chemistry 3] YDCN-700-10: (cresol novolac type epoxy resin, manufactured by Nippon Steel Chemical & Materials Co., Ltd.) In addition, the following substances were used as flame retardants. Exolit (registered trademark) OP-930: (organic phosphinate metal salt, Clariant) BCA: (organic phosphorus compound, 9,10-dihydro-10-benzyl-9-oxa-10-phosphaphenanthrene-10-oxide, Sanko Co., Ltd.)

[0094] (Example 1) 40 parts by mass of the copolyester (a1) obtained in the above synthesis example was dissolved in toluene to prepare a toluene varnish having a solid content concentration of 40% by mass. To the varnish, 2 parts by mass of EP-3950E and 1 part by mass of TETRAD X as a curing agent and 10 parts by mass of Exolit OP930 as an organic phosphinate metal salt were mixed with 100 parts by mass of the polyester resin (a1) to prepare an adhesive composition (F1). The adhesive composition (F1) obtained was subjected to various evaluations of adhesiveness, solder heat resistance, resin bleeding, flame retardancy, and long-term heat resistance.

[0095] (Examples 2 to 9, Comparative Examples 1 to 7) Adhesive compositions (F2) to (F16) were prepared in the same manner as in Example 1 except that the types and blending amounts of the polyester resin (A) and the epoxy resin (B) were changed as shown in Table 1, and each evaluation was performed.

[0096] (Evaluation of Adhesive Composition) (Adhesion (peel strength)) An adhesive composition is applied to one side of a 12.5 μm thick polyimide film (Apical (registered trademark), manufactured by Kaneka Corporation) until the thickness after drying reaches 25 μm, and then dried at 130°C for 3 minutes. The adhesive film (B-stage product) thus obtained is bonded to a rolled copper foil (Espanex series, manufactured by Nippon Steel Chemical & Materials Co., Ltd.) having a thickness of 18 μm. The bonding is performed by pressing at 170°C and a pressure of 2 MPa for 280 seconds in such a way that the shiny surface of the rolled copper foil is in contact with the adhesive layer. Subsequently, the film is cured by heat treatment at 170°C for 3 hours to obtain a sample for peel strength evaluation. The peel strength is measured under the conditions of 25°C, film traction, tensile speed of 50 mm / min, and 90° peeling. This test is the bonding strength at room temperature. <Evaluation Criteria> ○: 1.0N / mm or more △: 0.5N / mm or more and less than 1.0N / mm ×: less than 0.5N / mm

[0097] (Solder heat resistance) Samples were prepared in the same manner as above, and a 2.0 cm×2.0 cm sample piece was immersed in a molten solder bath at 288° C. to check for changes in appearance such as blistering. <Evaluation Criteria> ◎: No bubbles for more than 60 seconds ○: Bubbling occurs within 30 seconds or more and less than 60 seconds ×: Bubbling occurs within 30 seconds

[0098] (resin overflow) An adhesive composition is applied to one side of a polyimide film having a thickness of 12.5 μm (Apical (registered trademark) manufactured by Kaneka Co., Ltd.) to a thickness of 25 μm after drying, and dried at 130°C for 3 minutes. The adhesive film (B-stage product) thus obtained is bonded to a substrate having a circuit formed on a rolled copper foil having a thickness of 18 μm (Espanex series manufactured by Nippon Steel Chemical & Materials Co., Ltd.) at a spacing of 100 μm. The bonding is performed by pressing at 170°C and a pressure of 2 MPa for 280 seconds in such a way that the circuit surface is in contact with the adhesive layer. The amount of adhesive flowing out from the bonding surface along the circuit is measured using a microscope. This test is used to evaluate the circuit embedding property and the suppression of resin overflow. When the measured value is less than 0.050 mm, the circuit embedding property cannot be satisfied. In addition, when the measured value is greater than 1.00 mm, the resin overflows excessively. <Evaluation Criteria> ◎: 0.10mm or more and less than 0.30mm ○: 0.050 mm or more and less than 0.10 mm or 0.30 mm or more and less than 0.50 mm △: 0.50mm or more and less than 1.00mm ×: less than 0.050mm or more than 1.00mm

[0099] (Flame retardancy) The adhesive composition was applied to both sides of a 12.5 μm thick polyimide film (Apical 12.5NPI manufactured by Kaneka Corporation) to a thickness of 16 μm after drying, dried at 130°C for 3 minutes, dried in an oven, and then heat-cured at 170°C for 3 hours to prepare a sample. The flame retardancy was evaluated based on the UL-94VTM flame retardancy standard. <Evaluation Criteria> ○: Equivalent to UL94 VTM-0. ×: Does not satisfy UL94 VTM-0.

[0100] (Long-term heat resistance (peel strength)) An adhesive composition was applied to one side of a 12.5 μm thick polyimide film (Apical (registered trademark), manufactured by Kaneka Co., Ltd.) until the thickness after drying reached 25 μm, and the film was dried at 130°C for 3 minutes. The adhesive film (B-stage product) thus obtained was bonded to a rolled copper foil (Espanex series, manufactured by Nippon Steel Chemical & Materials Co., Ltd.) with a thickness of 18 μm. The bonding was performed by pressing at 170°C and 2 MPa for 280 seconds in such a way that the shiny surface of the rolled copper foil was in contact with the adhesive layer. Subsequently, the film was cured by heat treatment at 170°C for 3 hours to obtain a sample for evaluating the peel strength. The sample was left standing in an oven at 150°C in an air atmosphere for 1000 hours, and the peel strength after 1000 hours was measured. The peel strength was measured under the conditions of 25°C, film traction, tensile speed of 50 mm / min, and 90° peeling. This test demonstrates the long-term reliability of the bonding strength. <Evaluation Criteria> ◎: 0.5N / mm or more ○: 0.2N / mm or more and less than 0.5N / mm ×: less than 0.2N / mm

[0101] [Table 1]

[0102] As is clear from Table 1, Examples 1 to 9 are adhesive compositions containing a polyester resin (A) and at least two epoxy resins (b) having nitrogen atoms, one of the two epoxy resins being (b1) and the other being (b2); or one being (b3) and the other being (b4), and any of the adhesive compositions are excellent in adhesion, solder heat resistance, and long-term heat resistance, and also satisfy circuit embedding properties and suppression of resin overflow. On the other hand, the adhesive compositions of Comparative Examples 1 to 3 cannot satisfy circuit embedding properties and suppression of resin overflow because only one epoxy resin (b) having nitrogen atoms is used; and in Comparative Example 4, a cresol novolac type epoxy resin is used as the epoxy resin (B), and no epoxy resin (b) having nitrogen atoms is used, and therefore long-term heat resistance cannot be satisfied. Since Comparative Example 5 does not contain epoxy resin (B), all the evaluations except for flame retardancy cannot be satisfied. Since polyamide-imide is used in Comparative Example 6 and acid-modified polypropylene is used in Comparative Example 7 instead of polyester resin (A), long-term heat resistance cannot be satisfied. Thus, in Comparative Examples 1 to 7, all the characteristics of adhesiveness, solder heat resistance, long-term heat resistance, circuit embedding property, and suppression of resin bleeding cannot be satisfied at the same time. Industrial Applicability

[0103] The adhesive composition of the present invention is excellent in adhesiveness and solder heat resistance, further exhibits long-term heat resistance, has good circuit embedding properties, and can suppress excess resin bleeding, and is therefore useful as an adhesive for FPCs for automotive applications.

Claims

1. An adhesive composition comprising a polyester resin (A) and an epoxy resin (B), wherein the epoxy resin (B) comprises at least two epoxy resins (b) having nitrogen atoms, wherein one of the two epoxy resins is the following epoxy resin (b1), and the other is the following epoxy resin (b2), (b1) a resin having a functionality of less than 3, (b2) Resins having four or more functional groups.

2. An adhesive composition comprising a polyester resin (A) and an epoxy resin (B), wherein the epoxy resin (B) comprises at least two epoxy resins (b) having nitrogen atoms, one of the two epoxy resins being the following epoxy resin (b3), and the other being the following epoxy resin (b4), (b3) a resin having a nitrogen atom which is not contained in the aromatic ring and is not adjacent to the aromatic ring, (b4) Resins having nitrogen atoms other than (b3). 3 . The adhesive composition according to claim 1 , wherein the epoxy resin (b) having a nitrogen atom comprises a glycidylamine type epoxy resin. 4 . The adhesive composition according to claim 1 , wherein the content of the epoxy resin (B) is 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the polyester resin (A). 5 . The adhesive composition according to claim 1 , further comprising an organic phosphinate metal salt (C). 6 . An adhesive sheet comprising an adhesive layer composed of the adhesive composition according to claim 1 or 2. 7 . A laminate comprising the adhesive sheet according to claim 6 .

8. A printed wiring board comprising the laminate according to claim 7 as a constituent element.

Citation Information

Patent Citations

  • flame retardant coverlay film

    JP1994104813B2

  • Backboard module

    JP2022172590A